Classification Comparison: Autism Spectrum Rating Scale and the ADOS-2 in an Underserved Rural Appalachian Setting. Issue 3 (3rd July 2022) - Simpson, Allison; Bundy, Myra Beth; Wygant, Dustin B.
ABSTRACT: Introduction: With the increasing prevalence of Autism Spectrum Disorder (ASD) in recent years, there has been a significant interest in diagnostic accuracy and patterns of autism. Behavior checklists, such as the Autism Spectrum Rating Scale (ASRS), are widely used in psychological evaluations, and while some evidence supports their use in autism assessment, there is some question about their validity, especially when compared to comprehensive measures and behavioral observations. Method: The current study used ADOS-2 diagnostic classifications as a measure of "ADOS-2 ASD" and compared this classification to ASRS parent and teacher ratings, with an aim of assessing the discriminant (diagnostic) validity of the ASRS. Results: Analyses indicated that parent and teacher ASRS report scores were not significantly different for individuals with and without autism as indicated by ADOS-2 classification. Conclusion: Implications of this preliminary research as well as future directions are suggested, including a concern that the ASRS may not provide the specific information needed to assist clinicians in differentiating between children who do or do not meet ASD diagnostic criteria.